Systematic review of diplommatinid land snails (Caenogastropoda, Diplommatinidae) endemic to the Palau Islands. (3) Description of eight new species and two new subspecies of Hungerfordia - Yamazaki, Midori; Yamazaki, Kazunori; Rundell, Rebecca, J.; Ueshima, Rei (Zootaxa, 2015)
Hungerfordia Beddome, 1889 is a land snail genus of the family Diplommatinidae, which shows extensive endemic radiation in the Palau (Belau) islands. Although 42 species or subspecies of the genus have been named to date, many species remain to be described. In this article, we describe ten new taxa of the genus: H. goniobasis exserta subsp. nov., H. ngereamensis sp. nov., H. spiroperculata sp. nov., H. fragilipennis sp. nov., H. brachyptera sp. nov., H. elegantissima anomphala subsp. nov., H. nodulosa sp. nov., H. irregularis sp. nov., H. chilorhytis sp. nov., H. globosa sp. nov.